"Poznaj Swój Kraj". O wartości poznawczej i innych wartościach w miesięczniku krajoznawczo-turystycznym = "Discover your country". On cognitive value and other values in the tourist and travel monthly magazine - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the article is to present the values described in one issue of the magazine "Poznaj Swój Kraj. Miesięcznik Krajoznawczo-Turystyczny" ("Discover Your Country. Tourist and Countryside Monthly Magazine"). Referring to the cognitive values expressed explicitly in the title, I present the semantic fields that the authors combine with the concept of the country. It is both his land and culture, and the people who shaped it in the past and shape it now. I also point out the sty?listic features of the language, because they also have an axiological dimension, indicating what is good and moving. On the basis of contexts, I also extract such values as aesthetic, ethical ones (e.g. social, sacred) which can be found in the magazine.
Keywords: wartość; kraj; język; poznanie; piękno; values; country; language; cognition; beauty